PKM KOPERASI SERBA USAHA “KSU” SEDANA GRAHA - Ni Luh Putu Yesy Anggreni; I Ketut Westra; I Putu Eka Indrawan (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
This Community Service Activity (PKM) aims to provide knowledge and skills for KSU Sedana Graha employees in general, especially those who have attended training on the use of digital marketing media to be able to apply and apply it in expanding marketing. This activity was held on 1 – 2 November 2019 in the KSU Sedana Graha meeting room, this activity was attended by 19 employees. In an all-digital era, it is deemed necessary to increase employee knowledge in order to compete with competitors.